# Solution

Pramod is 28 years old and his father is 58.

Let Pramod's age be y and that of his father be x. Then, x - y = 30 and xy = 1624.

Therefore, (x-y)^{2} = 900. That is, x^{2} - 2xy + y^{2} = 900.

Now, x^{2} - 2xy + y^{2} = 900 can be re-written as:
x^{2} + 2xy + y^{2} - 4xy = 900.

But, x^{2} + 2xy + y^{2} = (x + y)^{2}.

Therefore, (x + y)^{2} - 4xy = 900.

We have xy = 1624. So, 4xy = 4 x 1624 = 6496.

Therefore, (x + y)^{2} - 6496 = 900. So, (x + y)^{2} = 7396.

Therefore (x + y) = square-root (7396). Therefore, x + y = + or - 86. But we are considering ages and, so, x + y cannot be negative. So, (x + y) = 86.

Now, (x + y) = 86 and (x - y) = 30. Adding the two: 2x = 116; therefore x = 58. x - y = 30; so, 58 - y = 30. Therefore, y = 28.